Steady-State and Transient Relations: A Reply on Reswitching - Samuelson, Paul A. (Quarterly Journal of Economics, 1975)
Nature of a pitfall, 41.—Substantive vindication— 43.—Deeper issue of nonsteady-state analysis, 45.